Toughening of PZT ceramics by In-situ complex structures - Thongmee N. (2014)
This research fabricated ceramics with formula (l-x)PZT - xBLT, when x = 0, 0.03, 0.05, 0.07, 0.10, 0.15 and 0.20 by a solid-state reaction method and sintered at a temperature of 1150 °C for 4 h with a heating/cooling rate of 5 °Cmin-1. Phase analysis using XRD indicated the existence of PZT-based solid solutions with corresponding lattice distortion. SEM micrographs of ceramic surfaces showed a typical grain structure for PZT-rich phase, while a plate-like structure in BLT-rich phase was observed. PZT-rich ceramics possessed relatively high densities due to their more equiaxed grains with high packing capability compared with the ceramics with an addition of BLT. An addition of BLT generally decreased grain size of the ceramics. Mechanical properties such as hardness and fracture toughness could be enhanced significantly with small addition of complex structure BLT. © 2008 Trans Tech Publications, Switzerland.